Assessing Age-Related Changes in Corneal Densitometry Parameters With Anterior Segment OCT Speckle - Fojcik, Aleksandra; Kościółek, Aleksandra; Iskander, D. Robert (Translational vision science & technology, 2023)
The purpose of this study was to assess in vivo regional variability in the densitometry parameters of corneal stroma and the modulating effect of age on those parameters using statistical characterization of optical coherence tomography (OCT) speckle. OCT imaging of central and peripheral cornea was performed in a group of 20 younger (24 to 30 years old) and 19 older (50 to 87 years old) subjects. The sample size was estimated using normal assumptions and previously reported data on speckle parameter variability. Statistical parameters of corneal OCT speckle were calculated in the regions of interest (ROI) encompassing central and peripheral stroma as well as taking into account their anterior and posterior subregions. Both parametric (Burr-2 parameters: α and k) and a nonparametric approach (contrast ratio [CR]) were considered. Two-way analysis of variance was used to test for differences in densitometry parameters with respect to ROI position and age. Both approaches showed statistically significant differences within the ROI positions (all P < 0.001 for α, k, and CR) and age (P < 0.001, P = 0.002, and P = 0.003, for α, k, and CR, respectively) indicating substantial stromal asymmetry. Additionally, CR showed statistically significant differences between anterior and posterior subregions (P < 0.001). Corneal OCT-based densitometry is inherently asymmetrical and are influenced by age. The results indicate that regional variability of stromal structure is not limited to the central and peripheral regions but that differences exist also between the nasal and temporal parts of the cornea. The in vivo acquired parameters of corneal OCT speckle can be used to indirectly assess corneal structure.